Robot-assisted Partial Nephrectomy with Segmental Renal Artery Clamping: A Single Center Experience - Basatac, Cem; Akpinar, Haluk (Urology Journal, 2019)
Purpose: The aim of our study is to evaluate the feasibility and effectiveness of robotic partial nephrectomy performed with segmental clamping of tumor-feeding arteries. Materials and Methods: Thirty-six patients with renal tumor who underwent robotic partial nephrectomy with segmental renal artery clamping were included in this study. Prospectively recorded patient demographics, mean operation time, estimated blood loss, warm ischemia time, length of hospital stay, pre- and postoperative renal functions and oncological outcomes were analyzed retrospectively. All complications were graded based on the modified Clavien-Dindo classification system. Surgical success was defined as no conversion from segmental artery clamping to the main renal artery clamping. Results: Mean tumor size was 40 mm and, R.E.N.A.L nephrometry score was 6.74. Mean operation time, estimated blood loss and warm ischemia time were 162 min, 236 ml, and 16 min, respectively. Five postoperative complications were observed. There were no significant differences in terms of renal functional outcomes before and after surgery (P = .18). Of 36 patients, 34 were completed successfully; however, main renal artery clamping was required in two patients due to excessive bleeding from the tumor bed. The success rate of the segmental renal artery clamping technique was determined as % 94.4 (34/36) in our study. Conclusion: Segmental renal artery clamping may be considered as a reliable and effective surgical method for vascular control during robotic partial nephrectomy. For this technique, tumor characteristics and intrarenal vascular anatomy should be precisely evaluated by the preoperative contrast-enhanced computerized tomography with 3-D reconstruction.